(untitled) (Journal for Studies in Humanities and Social Sciences, 2015)
In Namibia the majority of orphans and vulnerable children are absorbed into the extended family structure. Out of an orphan population of 150 000 only a small number (729) is taken in by the 36 registered Residential Child Care Facilities (RCCFs) and 533 by unregistered RCCFs. There is, however, little discussion on who in the extended family does the caring or the gendered nature of that care. Women are the primary care givers of orphans and vulnerable children. This socially necessary reproductive labour is not enumerated or remunerated. The majority of households that take in orphans and vulnerable children are headed by elderly females who themselves depend on social transfers and remittances. The additional care burden exacerbates the crisis of social reproduction in affected households. Social Capital theorists, see women’s social reproductive labour as instrumental to reducing the care burden on the state. Feminist Social Reproduction theorists see it as contributing to social inequalities. Research in Namibia reveals the crises of social reproduction in AIDS affected households. This includes food insecurity, income insufficiency and the exclusion from services. Many affected households cannot access the social grants available due to social, economic and administrative barriers. This paper argues for the validation of women’s unpaid social reproductive labour in order to break the cycle of poverty and marginalization caused by AIDS. It argues for the inclusion of unpaid care work into macroeconomic frameworks.